Analysis of selected health problems of elderly patients - Mziray, Marzanna; Żuralska, Regina; Gaworska-Krzemińska, Aleksandra; Domagała, Przemysław; Kosińska, Teresa; Postrożny, Danuta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Physiological aging is manifested in qualitative and quantitative changes occurring in all body organs and systems. In subsequent ages decreases the efficiency of the regulatory mechanisms and adaptation to changing environmental conditions, the system reduces the resistance to harmful bacterial, viral and mental stress, diseases appear. These disorders are made worse under the influence of bad lifestyle, including inadequate physical activity. The aim of study. The aim of the presented study was to diagnose health problems in the elderly, during the standard home nursing visit environments and to understand the factors that cause their occurrence. Material and methods. The study was conducted on 104 people aged over 60 years who are using the medical services in Brzeźno NZOZ Clinic. The study used the method of diagnostic survey, questionnaire based on the technique of using a questionnaire survey of his own design. Results. The health status of seniors depend on their ages — the older the persons the lower they assess their mood. The most common diseases in the elderly are rheumatic diseases, diseases of the movement organs or musculoskeletal systems, and hypertension. Conclusions . More than 66% of seniors spend their free time passive. Preventive care take an important place in the lives of seniors and the information obtained from doctors and nurses have a significant impact on respondents’ decision about healthy behaviors. Nursing Topics 2014; 22 (1): 62–67